A comprehensive study on the thermo-mechanical properties of multi-walled carbon nanotube/epoxy nanocomposites. (June 2016) - Yas, Mohammad H; Mohammadi, Samira; Astinchap, Bandar; Heshmati, Mahmood
In this study, the mechanical, thermal and viscoelastic properties of multi-walled carbon nanotube/epoxy nanocomposite at low-weight percentages of nanotubes are evaluated and discussed. In order to provide better interfacial interactions of constituent materials, the multi-walled carbon nanotubes are functionalized with combination of H2 SO4 /HNO3 . Dynamic-mechanical thermal analysis test and hot plate thermal conductivity are performed to characterize temperature-dependent mechanical and thermal properties. Our results indicate that applying low weight fractions of functionalized multi-walled carbon nanotubes can effectively improve the elastic storage modulus (∼47%) and thermal conductivity (∼36%) as a function of temperature. All steps and characterization are described in detail. For higher concentration of multi-walled carbon nanotubes, SEM characterization of the fracture surfaces of the samples reveals that agglomeration of the nanotubes is the main reason for degradation of the properties. Moreover, based on experimental data, an elastic model has been presented to predict the obtained temperature-dependent elastic modulus.